Omega-3 and -6 fatty acid plasma levels are not associated with liver cirrhosis-associated systemic inflammation. - Katharina Maria Schwarzkopf; Alexander Queck; Dominique Thomas; Carlo Angioni; Chengcong Cai; Ylva Freygang; Sabrina Rüschenbaum; Gerd Geisslinger; Stefan Zeuzem; Christoph Welsch; Christian Markus Lange (PLoS ONE, 2019)
BACKGROUND:Liver cirrhosis is associated with profound immunodysfunction, i.e. a parallel presence of chronic systemic inflammation and immunosuppression, which can result in acute-on-chronic liver failure (ACLF). Omega-3 fatty acids are precursors of pro-resolving mediators and support the resolution of inflammation. OBJECTIVE:The aim of this study was to determine plasma levels of omega-3 fatty acids in patients with liver cirrhosis and ACLF. METHODS:Patients with liver cirrhosis with and without ACLF were enrolled in a prospective cohort study and analyzed post-hoc for the present sub-study. Clinical data and biomaterials were collected at baseline and at day 7, 28 and after 3 months of follow-up. Plasma concentrations of arachidonic acid (ARA) and docosahexaenoic acid (DHA), which represent key omega-6 and -3 fatty acids, respectively, were quantified and associated with markers of systemic inflammation and severity of liver cirrhosis. RESULTS:A total of 117 patients were included in the present analyses. Of those, 26 (22.2%), 51 (43.6%) and 40 (34.2%) patients had compensated or decompensated liver cirrhosis, and ACLF. Plasma levels of ARA and DHA were similar in patients with compensated cirrhosis, decompensated cirrhosis, and ACLF. Furthermore, no significant association between plasma ARA or DHA and C-reactive protein or peripheral blood leukocytes were observed (P>0.05). CONCLUSION:In our study plasma levels of key omega-3 and omega-6 fatty acid are neither associated with the severity of liver cirrhosis nor with liver-cirrhosis-associated systemic inflammation.